Word Stress in Chinese and Ukrainian Languages: Problems of Typology - Yastreblyanska, Mariya (Mediterranean Journal of Social Sciences, 2012)
The article analyzes and compares the accent system of two typologically different languages, Ukrainian and Chinese.Comparative analysis of accent system of these provide the basic data to determine phonetic error also can help to preventmistakes and facilitate general comprehension on a prosody level to which word stress belongs. It is important to emphasize thatthis study deals with word stress only in two-syllable Chinese words. Special attention is paid to the study of word stress inChinese Language (Mandarin) for a Ukrainian audience. Ukrainian and Chinese languages represent different types oflanguages. Ukrainian belongs to Slavic group, and is a flectional type; Chinese belongs to the Sino-Tibetan family, and is anisolating syllabic type language. Phonetical system of these two languages is different, which is the main reason Ukrainian nativespeaker have trouble mastering the Chinese phonetical system. Improper application of word stress can render communicationdifficult or even impossible. Comparative research of these two phonetically systems can help in the development of studyingmaterials based on the phonetic features of Ukrainian and Chinese. Thus, the aim of the article is, first, to determine accentrhythmsystem in Ukrainian and Chinese language traditions. Secondly, compare the word stress in different types of languages,namely flectional and isolating. Word stress helps to organize syllables into one language unit; this language unit has a certainaccent-rhythm structure.